2016
DOI: 10.1177/1474704916678217
|View full text |Cite
|
Sign up to set email alerts
|

What If the Rival Drives a Porsche?

Abstract: Previous research found that men conspicuously consume luxury products to attract a mate and to signal their mate value. However, these studies have yet neglected to investigate the function of male conspicuous consumption in same-sex competition. Given that intersexual selection and intrasexual selection are closely related processes, it stands to reason that a further function of male conspicuous consumption could be to impress and deter same-sex rivals. An 2 (intrasexual competition context vs. control) Â 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 57 publications
(106 reference statements)
2
40
1
Order By: Relevance
“…Women, on the other hand, reported to be more jealous when the rival was physically attractive. This confirms that heterosexual men and women will be particularly vigilant of those rivals possessing the attributes that they think the opposite sex values (Fink et al 2014;Hennighausen et al 2016). Because jealousy predicts mate-retention behaviours (Davis et al 2018), we predict that compared to men, women will report higher intentions to use mate-retention behaviours when the rival is described as attractive.…”
Section: The Current Studysupporting
confidence: 75%
See 1 more Smart Citation
“…Women, on the other hand, reported to be more jealous when the rival was physically attractive. This confirms that heterosexual men and women will be particularly vigilant of those rivals possessing the attributes that they think the opposite sex values (Fink et al 2014;Hennighausen et al 2016). Because jealousy predicts mate-retention behaviours (Davis et al 2018), we predict that compared to men, women will report higher intentions to use mate-retention behaviours when the rival is described as attractive.…”
Section: The Current Studysupporting
confidence: 75%
“…Because men find women with those attributes more attractive (Fletcher et al 2004), other women will perceive them as a greater threat. Hennighausen et al (2016) reported a similar process in men. Specifically, men prefer luxury cars compared to non-luxury ones and reported higher intentions to buy the luxury cars.…”
Section: Intrasexual Competition and Mate Retention: The Threat Of Mamentioning
confidence: 70%
“…Perhaps the cheerleader effect also occurs through a process of social inference, wherein observers use the presence of other faces in the group to infer that the evaluated individual likely possesses desirable characteristics, such as being friendly or kind, which consequently increases their perceived favourability to the observer 62 . Importantly, this type of social learning is not specific to mate selection 63 , or even to the presence of human faces, since favourable characteristics, including attractiveness, are attributed to faces shown with possessions that signal wealth or social status [64][65][66][67][68][69][70] . Therefore, a social inference mechanism could also explain why a small increase in attractiveness is found for faces shown among groups of houses.…”
Section: Discussionmentioning
confidence: 99%
“…The very same behaviour tendencies are linked to those who enjoy possessing prestigious objects like, for instance, cars (O'Cass and McEwen 2004;Truong and McColl 2011). To add another conjoining aspect, those with a strong power need are seen as showy, boastful and less agreeable (Engeser and Langens 2010) and are therefore similarly perceived as individuals who strongly value prestigious objects (Hennighausen et al 2016;Sung et al 2015). Based on the findings supporting a strong link between the need for power and prestigious objects, the power need is perceived to strongly match the reward prestigious company car.…”
Section: Matching Of Needs and Rewardsmentioning
confidence: 91%